Digital innovation and social hub building a sustainable digital economy through livelihood and community enrichment - Perez De Tagle, Micah T.
During the COVID-19 pandemic digital technology was a key element in maintaining and pushing forward the status quo. Within the Philippines, many MSMEs and individuals felt incapable to deal with the sudden shift into the digital. Meanwhile, concepts such as the Fourth Industrial Revolution (FIRe), Smarter Cities and Twin Transition, suggest the inevitability of an increasingly digital economy. With the fastpaced development and adoption of new technologies, there is an increased risk of unsustainable growth which can manifest as job losses, increased cyber security threats, and social alienation, etc. For the local economy to endure and proceed into the future, there needs to be accessible digital innovation empowering Filipino citizens to have up-to-date skills, resilient business strategies, higher digital literacy rates, among others. In addition, a holistic sustainable approach requires community enrichment as social interaction bolsters innovation. Therefore, this CDP seeks to determine a sustainable innovation-enabling platform within the Philippine context for the country's advancement into a digital next normal.